Would John Stuart Mill Support or Reject Net Neutrality? - L. Buresh Donald (Journal of Human Psychology, 2021)
In this article, the philosophy of John Stuart Mill is applied to the notion of net neutrality. It is argued that Mill would support net neutrality, provided it does not come in conflict with the principles of capitalism. The essay posits that Mill would contend that net neutrality would be supported if it promoted the greatest good for the greatest number of people. On the other hand, Mill would be against net neutrality if it harmed others, particularly those individuals without market power. The article observed that Mill believed that the purpose of government is to ensure the welfare of the people. In general, the paper concludes that Mill would probably have supported net neutrality.
Keywords: Good of the Many